From Collective Memory to Media Memory: Digital Environments in Memory Construction - Birgül Üstünbaş Erdoğan (4. Boyut Medya ve Kültürel Çalışmalar Dergisi)
Memory studies play an important role in the process of individuals and societies understanding and interpreting the past. The collective mental structure called collective memory enables a society to develop a meaningful understanding of historical events, cultural heritage and common values. Media is at the centre of this process; it enables the transfer of information, emotions and experiences between individuals and groups; In this way, it has critical importance in the formation and reshaping of collective memory. Today, there is an increasing tendency to find new ways to integrate contemporary media developments into collective memory studies. The development of digital technologies and network-based applications has taken memory studies to a different dimension and provided a broad framework for understanding how memory practises change. The aim of this study was to examine the role of digital environments in memory construction, focusing on the relationship between collective memory and digital media. In this context, the study is based on theoretical discussions. With the development of digital media technology, it is aimed to draw a framework regarding the relationship between different media environments and collective memory and to provide a perspective for studies in the field.